Potensi Virus A/Ck/West Java/PWT-Wij/2006 Sebagai Vaksin - Indriani, R.; Dharmayanti, NLP; Adjid, R.M.A.; Darminto, Darminto (JURNAL BIOLOGI INDONESIA, 2011)
ABSTRACTPotential virus A/Ck/West Java/PWT-Wij/06 for Vaccin. Vaccination program for controllingavian influenza (AI) virus infection in poultry have been emerged during the past 5 years inIndonesia. However, due to the mutation character of this virus the available vaccines were nolonger effective. Therefore a new local isolate of avian influenza virus A/Ck/West Java/Pwt-Wij/2006 was studied. The virus, formulated as inactive vaccine, was injected in to 3 weeks oldof layer chickens intramuscularly. At 3 weeks after vaccination, vaccinated chickens werechallenged against seven local isolates of HPAI H5N1 intranasaly. Unvaccinated chickenswere included in the challenge test as control. Results showed that the vaccine produced100% protection against A/Ck/West Java/Pwt-Wij/2006 (homologous), A/Ck/West Java/1067/2003, A/Ck/West Java/Hj-18/2007, and A/Ck/Payakumbuh/BPPVRII/2007; produced 90%protection against A/Ck/BB149/5/2007, and 80% protection against A/Ck/West Java/Hamd/2006 isolates. The vaccine also stoppped viral shedding by day 5 to 7 after challange. Thisstudy indicate that the new local isolate of avian influenza A/Ck/West Java/Pwt-Wij/2006 hasgood potency as vaccine with broad spectrum against a range of AI viruses available inIndonesia.Key words: avian influenza, HPAI, H5N1,vaccine, poultry.